2021
DOI: 10.1002/chem.202103817
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Polyoxometalate Platforms for Supramolecular Light‐Driven Hydrogen Evolution**

Abstract: Multifunctional supramolecular systems are a central research topic in light-driven solar energy conversion.Here, we report a polyoxometalate (POM)-based supramolecular dyad, where two platinum-complex hydrogen evolution catalysts are covalently anchored to an Anderson polyoxomolybdate anion. Supramolecular electrostatic coupling of the system to an iridium photosensitizer enables visible light-driven hydrogen evolution. Combined theory and experiment demonstrate the multifunctionality of the POM, which acts a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 83 publications
(156 reference statements)
0
4
0
Order By: Relevance
“…As shown in several previous reports, replacement of the chloride ligands by iodide ligands typically enhances light-induced hydrogen evolution in Pt-based systems. 19,48,49 For instance, Kaufhold et al 48 showed that the addition of an iodide salt to the photocatalytic system can activate a platinum center during photocatalysis by in situ ligand exchange leading to improved H 2 formation.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in several previous reports, replacement of the chloride ligands by iodide ligands typically enhances light-induced hydrogen evolution in Pt-based systems. 19,48,49 For instance, Kaufhold et al 48 showed that the addition of an iodide salt to the photocatalytic system can activate a platinum center during photocatalysis by in situ ligand exchange leading to improved H 2 formation.…”
Section: Resultsmentioning
confidence: 99%
“…740 after 10 hours. 174 In 2022, the Yang group reported a pure-inorganic, bis-Sb 3 O 3 -functionalized Anderson–Evans complex, namely [Ni(H 2 O) 6 ]KH[NiMo 6 O 24 (Sb 3 O 3 ) 2 ]·5H 2 O (Fig. 18c).…”
Section: Applicationmentioning
confidence: 99%
“…This work is therefore relevant to the growing area of molecular spintronics, as well as the important topic of structure prediction for molecular materials in general. While bifunctional and multifunctional molecular assemblies have been reported in the experimental literature previously, [29,30] the prediction of a bifunctional assembly entirely from computation appears to be a first.…”
Section: Introductionmentioning
confidence: 97%